Additional AM Fungi Inoculation Increase Populus cathayana Intersexual Competition - Wu, Qiuping; Tang, Yun; Dong, Tingfa; Liao, Yongmei; Li, Dadong; He, Xinhua; Xu, Xiao (Frontiers in Plant Science, 2018)
Sex-specific responses to mycorrhiza have been reported in dioecious plant species, but little attention has been paid to the influence of arbuscular mycorrhizal fungi (AM fungi) on competitive ability under intersexual competition. To further address whether this competition is affected by an additional AM fungi supply, Populus cathayana saplings were chosen and subjected to two mycorrhizal treatments (inoculated and non-inoculated (control) with an additional AM fungi Funneliformis mosseae) while growing with the opposite sex for three months. Compared with the control, the additional AM fungi inoculation induced P. cathayana saplings to exhibit significant sexual differences in root structure and nutrient uptake (e.g., cortical layer, cross section area, radius of root tips, and N, K and Mg content), and enlarged sexual differences in morphology and biomass accumulation (e.g., leaf number increment, shoot height increment, total leaf area, total specific root length, stem dry mass, leaf dry mass and total dry mass). Meanwhile, inoculated females presented higher values in most of these traits mentioned above than males under intersexual competition. Therefore, we conclude that the intersexual competition can be increased by an additional AM fungi supply, with females gaining more symbiosis-mediated benefits than males.